[Michaels, Axel, ed. Klassiker der Religionswissenschaft: von Friedrich Schleiermacher bis Mircea Eliade] - Gebelt, Jiří (Religio, 1999)
Reviewed works: Michaels, Axel, ed. Klassiker der Religionswissenschaft: von Friedrich Schleiermacher bis Mircea Eliade. München: C. H. Beck, c1997. 427 s. ISBN 3-406-42813-4.